1987
DOI: 10.1037/0022-006x.55.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peer support and therapist contact on long-term weight loss.

Abstract: This study evaluated the effectiveness of two posttreatment programs designed to enhance the maintenance of weight loss. Eighty-five obese clients were randomly assigned to either (a) behavior therapy plus a peer-support maintenance program, (b) behavior therapy plus a therapist-contact maintenance program, or (c) behavior therapy only. At a 7-month follow-up session, the therapist-contact program resulted in significantly greater maintenance of weight loss compared with the peer support and behavior therapy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 7 publications
1
69
0
2
Order By: Relevance
“…47 Second, we assessed studies according to the duration of follow-up (less than six months versus six months or longer), since it is known that early weight loss benefits are often not sustained over time. 48,49 Third, we also grouped studies by publication date, considering those published prior to 1995 as one group and those published in 1995 or after as another.…”
Section: Assessment Of Heterogeneitymentioning
confidence: 99%
“…47 Second, we assessed studies according to the duration of follow-up (less than six months versus six months or longer), since it is known that early weight loss benefits are often not sustained over time. 48,49 Third, we also grouped studies by publication date, considering those published prior to 1995 as one group and those published in 1995 or after as another.…”
Section: Assessment Of Heterogeneitymentioning
confidence: 99%
“…26,27,31 Blind outcome assessment was carried out in three of the studies, 20,22,27 the others were either not clear (six studies) or not done (three). 21,24,25 It was clear that there were no substantial baseline differences in only ®ve studies 25 ± 29 in a further two there were no baseline differences for some of the reported outcome measures, 20,21 in the other ®ve studies it was not possible to tell. In only two studies were reported outcomes clearly reliable, 22,27 whilst in the others it was not clear.…”
Section: 28 ± 30mentioning
confidence: 99%
“…Only ®ve studies had adequate duration of follow-up. 20,22,25,27,30 Four of the 12 studies reported interventions targeted at health professionals. One of these was essentially an organisational intervention encouraging shared care among health professionals.…”
Section: 28 ± 30mentioning
confidence: 99%
See 1 more Smart Citation
“…4 ± 6 Moreover, follow-up times after maintenance programmes have usually been for less than a year. 4,7 It is not known if they really improve long-term outcome or only delay weight regain.…”
Section: Problems Of Maintenance Programmesmentioning
confidence: 99%